Evidence of linkage of the inflammatory bowel disease susceptibility locus on chromosome 16 (IBD1) to ulcerative colitis. Issue 3 (March 1998) - Mirza, M M; Lee, J; Teare, D; Hugot, J P; Laurent-Puig, P; Colombel, J F; Hodgson, S V; Thomas, G; Easton, D F; Lennard-Jones, J E; Mathew, C G
Abstract : Crohn's disease (CD) and ulcerative colitis (UC) are inflammatory bowel diseases (IBD) of unknown aetiology which are characterised by chronic inflammation of the gastrointestinal tract. Epidemiological studies suggest the presence of a genetic component in the aetiology of both CD and UC. A susceptibility gene for Crohn's disease has recently been mapped to the pericentromeric region of chromosome 16 (IBD1), and this finding has been replicated in two subsequent studies. Although CD and UC are distinct clinical entities, the fact that both disorders occur in a significant proportion of families with multiple cases of IBD suggests that overlapping sets of susceptibility genes may be involved. We have addressed this question for IBD1 by typing eight microsatellite markers from the locus in 70 kindreds affected with either UC only or with both UC and CD and analysing the data for linkage by both non-parametric and parametric methods. Evidence for linkage was detected in families affected with only UC, with a mean proportion of 0.70 affected sib pairs sharing alleles identical by descent at D16S3136 (p=0.01), and a peak non-parametric linkage score of 2.02 at D16S3120 with the GENEHUNTER program (p=0.02). The estimated sib relative risk attributable to IBD1 in these families was 1.46. Surprisingly, no evidence of linkage was detected in the families affected with both UC and CD (p>0.2). The data suggest that IBD1 may also contribute to susceptibility to ulcerative colitis, and that it is likely to be located in the 12 cM interval between D16S419 and D16S409.